2020
DOI: 10.1021/acsomega.0c01063
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Flash Index: Powerful and Perspicuous Help for Efficient Separation System Design

Abstract: There are different factors and indices to characterize the performance of a pervaporation membrane, but none of them gives information about their capabilities in the area of liquid separation compared to the most convenient alternative, which is distillation. Membrane flash index (MFLI) can be considered the first and only one that shows if the membrane is more efficient or not than distillation and quantifies this feature too. Therefore, the MFLI helps select the best separation alternative in the case of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…MFLI was also used to evaluate the PV membranes' capabilities in liquid separation compared to traditional distillation. It can be seen that the graphene/PVA MMMs prepared in this work exhibited comparable or even higher MFLI values compared with other PVA-based MMMs reported in the literature, which indicated that pervaporation with these MMMs possessed better separation efficiency over flash distillation [44,45]. According to the results, it was presumed that graphene intercalated with an appropriate number of oxygen-containing groups might be a good choice to prepare PVA-based MMMs for ethanol dehydration, which would combine the advantages of GR's high interlayer diffusion selectivity and GO's high permeation properties and open a door to achieve both high permeation flux and the separation factor of MMMs by tuning the microstructure of graphene.…”
Section: Comparison Of Pv Performance Of Pva-based Mmmssupporting
confidence: 60%
See 1 more Smart Citation
“…MFLI was also used to evaluate the PV membranes' capabilities in liquid separation compared to traditional distillation. It can be seen that the graphene/PVA MMMs prepared in this work exhibited comparable or even higher MFLI values compared with other PVA-based MMMs reported in the literature, which indicated that pervaporation with these MMMs possessed better separation efficiency over flash distillation [44,45]. According to the results, it was presumed that graphene intercalated with an appropriate number of oxygen-containing groups might be a good choice to prepare PVA-based MMMs for ethanol dehydration, which would combine the advantages of GR's high interlayer diffusion selectivity and GO's high permeation properties and open a door to achieve both high permeation flux and the separation factor of MMMs by tuning the microstructure of graphene.…”
Section: Comparison Of Pv Performance Of Pva-based Mmmssupporting
confidence: 60%
“…Membrane flash index (MFLI) [44,45] is another simple and valuable method to evaluate the PV membranes' capabilities in liquid separation compared to traditional distillation, which is mainly based on the comparison of available theoretical maximum distillate compositions.…”
Section: Pervaporation Performance Measurementmentioning
confidence: 99%
“…Considering pervaporation and flash distillation options, a simple method to evaluate pervaporation and elementary flash distillation is as follows [ 31 ]: where MFLI means membranes flash index, is the permeate concentration and is the equilibrium distillation value.…”
Section: Theory Of Pervaporationmentioning
confidence: 99%